The story of two gardens: quran stories for little hearts - Khan, Saniyasnain (GoodwordKidz New Delhi, 2004)
This narrative contrasts the fortunes of two men, one blessed with a lush garden and the other with humble means. It serves as a moral lesson on gratitude, humility, and the transient nature of wealth.